2015
DOI: 10.1111/rda.12525
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sperm Concentration and Storage Vessel on Quercetin‐Supplemented Rabbit Semen During Chilled Storage

Abstract: Extending the shelf life of chilled rabbit spermatozoa is vital for the expansion of the farmed rabbit industry. This study evaluated the relationship between sperm concentration and packaging on in vitro quality of chilled rabbit semen over 96 h. Semen was collected from adult bucks (n = 4) and pooled at 37°C following evaluation. Pooled ejaculates were diluted with a Tris-based extender supplemented with 100 μm quercetin to a concentration of 15, 30 or 60 × 10(6)  spermatozoa/ml, packaged into plastic tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
3
12
0
1
Order By: Relevance
“…and apeginin-7-glucoside (1.113 mg/g extract) that have scavenging antioxidant activity against free radicals interpret the benefit beyond the enrichment of rabbit semen tris-based extender to overcome the lipid peroxidation process induced via chilling period [54][55][56][57][58][59]. This elongates the period of chilling in rabbit extended semen above 72 h in agreement with Di Lorio et al [9] and Johinke et al [10].…”
Section: Discussionsupporting
confidence: 75%
“…and apeginin-7-glucoside (1.113 mg/g extract) that have scavenging antioxidant activity against free radicals interpret the benefit beyond the enrichment of rabbit semen tris-based extender to overcome the lipid peroxidation process induced via chilling period [54][55][56][57][58][59]. This elongates the period of chilling in rabbit extended semen above 72 h in agreement with Di Lorio et al [9] and Johinke et al [10].…”
Section: Discussionsupporting
confidence: 75%
“…Researches showed that in case of using the ram semen within the short time after collection for artificial insemination, to avoid from freezing/thawing induced injuries, using cooled and diluted semen would be a practical alternative (King et al., ). The improvement in semen storage techniques requires in‐depth knowledge of the biochemical processes occurring during semen collection, dilution and processing (Johinke, de Graaf, & Bathgate, ; Yoshida, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, only sperm motility was affected by semen dilution, but not for sperm viability and acrosome integrity. There had been demonstrated in chilled semen that (i) the sperm plasma membrane was more resistant to osmotic stress than the mechanisms responsible for sperm motility, as seen in bull (Liu & Foote, ), boar (Fraser, Gorszczaruk, & Strzezek, ) and dog (Songsasen et al., ); (ii) the sperm viability and acrosome integrity were not differ among different extenders, while the motility was significantly affected, as seen in boar (Kaeoket, Srisowanna, Wichaidit, Chanapiwat, & Manee‐In, ) and donkey (Dorado et al., ); (iii) the sperm plasma membrane was altered after dilution only when final sperm concentration was 20 × 10 6 sperm/ml or less, as observed in bull (Garner et al., ); (iv) the sperm plasma membrane was not affected by semen dilution until 96 hr of cooled storage as shown in rabbit (Johinke et al., ). These indicated that the sperm motility was more susceptible to various conditions, than their plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A high dilution ratio could result in detrimental effects on semen quality, such as sperm motility, viability or acrosome integrity. This has been demonstrated in boar (Lipensky, Lustykova, Frydrychova, Rozkot, & Vaclavkova, ; Weitze, Le Thi, & Waberski, ), bull (Garner, Thomas, & Allen, ; Garner et al., ), stallion (Hayden et al., ; Varner, Blanchard, Love, Garcia, & Kenney, ), tomcat (Prochowska, Niżański, Ochota, & Partyka, ) and rabbit (Johinke, de Graaf, & Bathgate, ). This might due to the decreased concentration of seminal plasma (SP) (Maxwell & Johnson, ).…”
Section: Introductionmentioning
confidence: 89%